Development obstacles of the agent accounting industry in China’s Guangdong-Hong Kong-Macao Greater Bay Area based on quantitative analysis—Research on the problem of employee’s work attitude - Huang, Xiang; Lee, Hyukku; Wang, Mingyi; Wang, Dong; Wu, Yaoxian; Du, Kangsheng (Frontiers in Psychology, 2022)
The notion of “agent bookkeeping” was proposed when the “Accounting Law of the People’s Republic of China” was updated in 1993. Since their business is specialized in serving small and micro-enterprises, this has created the industry characteristic of generally small in the size of company and low in the salary of employees in Chinese agent bookkeeping companies. Such characteristic results in a series of problems including negative work attitude of employees in the development process, which seriously limit the development of Chinese agent bookkeeping companies. However, issues occurred in the development of agent bookkeeping, such as negative employee attitudes, which severely hampered the growth of Chinese agent bookkeeping companies. Therefore, a model of three dimensions of work attitude has been set up in this paper to demonstrate the working attitude of the staff of the agent bookkeeping companies in China’s Guangdong-Hong Kong-Macao Greater Bay Area, including emotional dimension, behavioral dimension, and cognitive dimension which consists of eight factors: work environment, career satisfaction, interpersonal relationship, role engagement, work vitality, responsibility attitude, emotional identity, and retention attitude. The result indicates that (1) female employees outnumber male ones in agent bookkeeping companies, (2) most employees have a low sense of belonging to the company, (3) limited career development affects employees’ enthusiasm for work, (4) work attitudes are influenced by mediocre work performance among employees with a graduate degree or higher.